Lacan's Psychoanalysis of the Manipulative Personality: Correlation of the Author's Desire with the Antagonist Nick Buckley in Hotel Majestic-Peril at End House - Ratri, Risalah Damar (Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
AbstractThis study focuses on trying to determine the correlation between author Agatha Cristie's desires and the manipulative character Nick Buckley in the novel Hotel Majestic – Peril at End House. Applying Jaques Lacan's psychoanalytic theory regarding the concept of desire which states that individuals will become subjects in an effort to fulfill their shortcomings. In this study, the results found were Agatha Cristie's desire as a writer to fight back against events that hurt her in life. Then the presence of an ideal image in the form of being recognized as a brave and great woman becomes the desire that Agatha Cristie strives for through the antagonist Nick Buckley. The third desire is the search for another object because of lost love. Then the fourth desire, in the form of presenting a manipulative character in Nick Buckley, becomes Agatha's way of fulfilling her desire to gain compassion or attention from readers and other characters in the novel. So the correlation between the creation of manipulative traits that secretly control other characters to obtain personal gain by Nick Buckley helps manifest Agatha Crishtie's passion as an author. Childhood life, death and divorce from her husband were the main factors in Agatha acting as the subject of the novel Hotel Majestic – Peril at End House.Key words: Lacan, desire, manipulative, Agatha Cristie, Nick Buckley